Diabetes mellitus no sistema privado de saúde: estudo do perfil de beneficiários de uma caixa de assistência médica no Distrito Federal - Hortêncio, Ana Paula Brito (2006)
Objectives. 1) Generality: To describe the profile of the demand of the diabetic ones, to the Services of assistance to the health in years of 2000 the 2004, through pointers of use and cost of the given assistance. 2) Specific: To evaluate the tax of casualty of the diabetic ones studied of 2004. Material and Methods. The numbers had been collected in the System of Management Information of the company - white of the study they are organized in five ages band (the 40 more than 80 years). The inclusion in the sample had been the associates of the submitted DF, to little, an annual examination of glucosilade hemoglobine , between the years of 2000 the 2004. The type of study is exploratory, descript and if it configures as demand analysis. Results. 44,99% of the associates of the box of medicai assistance, live in the DF, have age above of 40 years. The DF represents 6.51% of the total of associates of the box of medicai assistance of the country. 51,1% of the associate are of feminine sex and 48.9% of the masculine sex. It has a gradual growth in the number of associates who had carried through the examination of HG in the ones of 2000 the 2004. Between 40-49 years, it has the annual increase of that they make control of the illness. The diabetes mellitus is more prevalent in the women of whom it in the men. The diabetic ones look more the health Services. This frequency increases with the age. The diabetics men, in more advanced age, intern more of the one than the women; they have increased hospital permanence and they have percentile greater of cost to the company. The casualty of diabetes, in 2004, was of 127%; that is, the carriers of the illness had contributed less for the plan of health 27% of the one than they had spent. Conclusions: The study it demonstrates to the high representation of diabetes mellitus in the box of medicai assistance and sample that the prevalence of the illness increased of 81,3/1000 of 2000 for 175,5 2004 in the age band of 40 -59 years, being band of bigger risk for the manifestation of the type two diabetic.